Patterns of Prenatal Care Delivery and Obstetric Outcomes before and during the COVID-19 Pandemic - Kern-Goldberger, Adina R.; Sheils, Natalie E.; Ventura, Maria Eloisa M.; Paderanga, Ana Jane A.; Janer, Ciara D.; Donato, Patricia Rose B.; Asch, David A.; Srinivas, Sindhu K. (American Journal of Perinatology, 2023)
Objective Health care providers and health systems confronted new challenges to deliver timely, high-quality prenatal care during the coronavirus disease 2019 (COVID-19) pandemic as the pandemic raised concerns that care would be delayed or substantively changed. This study describes trends in prenatal care delivery in 2020 compared with 2018 to 2019 in a large, commercially insured population and investigates changes in obstetric care processes and outcomes.Study Design This retrospective cohort study uses de-identified administrative claims for commercially insured patients. Patients whose entire pregnancy took place from March 1 to December 31 in years 2018, 2019, and 2020 were included. Trends in prenatal care, including in-person, virtual, and emergency department visits, were evaluated, as were prenatal ultrasounds. The primary outcome was severe maternal morbidity (SMM). Secondary outcomes included preterm birth and stillbirth. To determine whether COVID-19 pandemic-related changes in prenatal care had an impact on maternal outcomes, we compared the outcome rates during the pandemic period in 2020 to equivalent periods in 2018 and 2019.Results In total, 35,112 patients were included in the study. There was a significant increase in the prevalence of telehealth visits, from 1.1 to 1.2% prior to the pandemic to 17.2% in 2020, as well as a significant decrease in patients who had at least one emergency department visit during 2020. Overall prenatal care and ultrasound utilization were unchanged. The rate of SMM across this period was stable (2.3–2.8%) with a statistically significant decrease in the preterm birth rate in 2020 (7.4%) compared with previous years (8.2–8.6%; p < 0.05) and an unchanged stillbirth rate was observed.Conclusion At a time when many fields of health care were reshaped during the pandemic, these observations reveal considerable resiliency in both the processes and outcomes of obstetric care.Key Points
Keywords: prenatal care; telehealth; maternal morbidity; preterm birth; stillbirth